2021
DOI: 10.5194/se-12-1865-2021
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the East African Limpopo margin, a strike-slip rifted corridor along the continental Mozambique Coastal Plain and North Natal Valley

Abstract: Abstract. Coincident wide-angle and multi-channel seismic data acquired within the scope of the PAMELA Moz3-5 project allow us to reconsider the formation mechanism of East African margins offshore of southern Mozambique. This study specifically focuses on the sedimentary and deep-crustal architecture of the Limpopo margin (LM) that fringes the eastern edge of the Mozambique’s Coastal Plain (MCP) and its offshore southern prolongation the North Natal Valley (NNV). It relies primarily on the MZ3 profile that ru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…Initially subject to a dexterous movement, the Mozambique Channel finally opened by oceanic expansion from the Middle Jurassic, as the Antarctic and Australian continents moved south and eastward away from Africa. South of the Mozambique Coastal Plain, the Natal Valley is a sedimentary basin above a 30 km thick continental crust, 1000 m below sea‐level, probably resulting from a subsidence induced by probable intrusions of mantle‐derived melts in the lower crust (Moulin et al ., 2020; Evain et al ., 2021; Leprêtre et al ., 2021).…”
Section: Regional Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially subject to a dexterous movement, the Mozambique Channel finally opened by oceanic expansion from the Middle Jurassic, as the Antarctic and Australian continents moved south and eastward away from Africa. South of the Mozambique Coastal Plain, the Natal Valley is a sedimentary basin above a 30 km thick continental crust, 1000 m below sea‐level, probably resulting from a subsidence induced by probable intrusions of mantle‐derived melts in the lower crust (Moulin et al ., 2020; Evain et al ., 2021; Leprêtre et al ., 2021).…”
Section: Regional Settingsmentioning
confidence: 99%
“…The Limpopo Corridor was supposed to be floored by oceanic crust, with emplacement during the opening of the Mozambique Basin as a northern extension of the magmatic Mozambique Ridge, south of the Naude ridge (Leinweber & Jokat, 2012; Mueller & Jokat, 2019). Combined wide‐angle and multi‐channel seismic studies and geodynamic studies have shown that the Limpopo Corridor is a strike‐slip margin with thin continental crust (Thompson et al ., 2019; Moulin et al ., 2020; Evain et al ., 2021; Li et al ., 2021; Watremez et al ., 2021). The positive gravity anomalies correspond to a series of bathymetric highs between 2000 m and 3000 m of water depth (Evain et al ., 2021), which were recognized as contourite drifts in seismic surveys (Wiles et al ., 2014; Thiéblemont et al ., 2019; Gao et al ., 2020; Li et al ., 2021) overlying mass transport deposits (MTD; Evain et al ., 2021).…”
Section: Regional Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several plate kinematic models based upon geological studies, potential field data, and seismic data propose reconstructed initial positions of Africa and Antarctica (Evain et al, 2021;Gaina et al, 2013;Klimke et al, 2018;Leinweber & Jokat, 2012;Reeves et al, 2016;Sahabi, 1993;Thompson et al, 2019). These plate kinematic models show that Africa and Antarctica were joined along what is now the Mozambique margin, before the break-up of Gondwana.…”
Section: Geological Settingmentioning
confidence: 99%
“…The source was composed of an array of 15 airguns, synchronized on the first peak and providing a total volume of 6,500‐in 3 , with shot interval every 60 s. The 2,974 air‐gun shots along MZ6 start slightly south of MZ6OBS01 (296 km model distance) extending 185 km south of MZ6OBS25 and were recorded by all instruments and a marine 720‐channel streamer 4.5 km in length. This profile runs parallel to the MZ7 profile (Leprêtre et al., 2021) about 80 km eastward and crosses the MZ1, MZ2, and MZ3 (Evain et al., 2021) profiles at the positions of the MZ6OBS18, MZ6OBS08, and MZ6OBS15, respectively. It presents therefore three crossing points that constrain our model.…”
Section: Methodsmentioning
confidence: 73%